Theoretical Calculation of Reorientation Energy in Metal /Semiconductor Interface - A-Agealy, H. J. M.; Mujbi, H. Kh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A theoretical calculation of the reorientation energy for non adiabatic electron transfer at interface between metal and semiconductor system was carried out. The continuum outer sphere theory of electron transfer reaction has been extensively used for electron transfer between metal/semiconductor interface .It is found that in these calculations the reorientation energy is proportional to the optical and statistical dielectric constant of semiconductor , properties of metal ,and the distance between metal and semiconductor .Results of reorientation energy show that ZnO semiconductor with metal Au possess a good matching ascompared with ZnS and ZnSe . Theoretical calculation showed a good agreement with experimental value.